2007
DOI: 10.1515/znc-2007-5-612
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Croton stellatopilosus Suspension Culture for Geranylgeraniol Production and Diterpenoid Biosynthesis

Abstract: Diterpenoids in higher plants are biosynthesized from isoprene units obtained from two distinct pathways: the mevalonate pathway and the deoxyxylulose phosphate pathway. The metabolic partitioning of both pathways in plant species is dependent upon the type of culture. In order to study the diterpenoid biosynthesis in Croton stellatopilosus cell culture, callus culture was firstly induced from C. stellatopilosus young leaves in Murashige and Skoog (MS) medium in the presence of 1.0 mg/l 2,4-dichlorophenoxyacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The suspension culture was induced as described previously. 12 It was maintained in Murashige and Skoog (MS) medium 14 supplemented with 2 mg/L of 2,4-dichlorophenoxyacetic acid (2,4-D), 2 mg/L of benzyladenine (BA) and 3% w/v sucrose. Growth curves and product formation during the growth cycle of the suspension culture were first established.…”
mentioning
confidence: 99%
“…The suspension culture was induced as described previously. 12 It was maintained in Murashige and Skoog (MS) medium 14 supplemented with 2 mg/L of 2,4-dichlorophenoxyacetic acid (2,4-D), 2 mg/L of benzyladenine (BA) and 3% w/v sucrose. Growth curves and product formation during the growth cycle of the suspension culture were first established.…”
mentioning
confidence: 99%
“…9) Earlier studies on the phytochemicals and their localization demonstrated that production of intermediates for terpenoid biosynthesis was related to chloroplastforming cells. 10,11) However for the early steps of isoprenoid biosynthesis in C. stellatopilosus, there is lack of knowledge about genes and enzymes, which have not as yet been reported. Therefore, the objective of this work is to study the genes encoding the 1-deoxy-D-xylulose 5-phosphate synthase (CSDXS) and 2C-methyl-D-erythritol 4-phosphate synthase (CSMEPS) from C. stellatopilosus.…”
mentioning
confidence: 99%